Prognostic value of hematogenous dissemination and biological profile of the tumor in early breast cancer patients: A prospective observational study - Gubern Josep M; Mariscal Antonio; Rull Miquel; Julian Juan F; Castellá Eva; Margelí Mireia; Solá Montserrat; Barnadas Agustí; Fraile Manuel (BMC Cancer, 2011)
Abstract Background The aim of this study was to investigate the incidence and prognostic value of disseminated tumor cells in bone marrow of breast carcinoma patients with early disease, and to analyze this finding in relation to lymph node involvement, determined by sentinel lymph node (SLN) biopsy analysis, and to prognostic factors of interest. Methods 104 patients with operable (T < 3 cm) breast cancer and clinically- and sonographically-negative axillary lymph nodes were scheduled for SLN biopsy. Bone marrow aspirates were collected before the start of surgery from both iliac crests, and mononuclear cell layers were separated by density centrifugation (Lymphoprep). Slide preparations were then examined for the presence of disseminated tumor cells by immunocytochemistry with anti-cytokeratin antibodies (A45-B/B3). Lymphoscintigraphy was performed 2 hours after intratumor administration of 2 mCi (74 MBq) of 99mTc colloidal albumin. The SLN was evaluated for the presence of tumor cells by hematoxylin-eosin staining and, when negative, by immunocytochemistry using anti-cytokeratin antibody (CAM 5.2). Survival analyses and comparative analyses were performed on the results of bone marrow determinations, SLN biopsy, and known prognostic factors, including breast cancer subtypes according to the simplified classification based on ER, PR and HER2. Results Lymph node and hematogenous dissemination occur in one-third of patients with early-stage breast cancer, although not necessarily simultaneously. In our study, disseminated tumor cells were identified in 22% of bone marrow aspirates, whereas 28% of patients had axillary lymph node involvement. Simultaneous lymph node and bone marrow involvement was found in only 5 patients (nonsignificant). In the survival study (60 months), a higher, although nonsignificant rate of disease-related events (13%) was seen in patients with disseminated tumor cells in bone marrow, and a significant association of events was documented with the known, more aggressive tumor subtypes: triple negative receptor status (21%) and positive ERBB2 status (29%). Conclusions Tumor cell detection in bone marrow can be considered a valid prognostic parameter in patients with early disease. However, the classic prognostic factors remain highly relevant, and the newer breast cancer subtypes are also useful for this purpose.